Etiologic Diagnosis of Lower Respiratory Tract Infections - Hoeprich, Paul D. (1970)
Decision as to the role of infection in lower respiratory tract disease requires examination by culture of specimens known to be derived from the infra-laryngeal respiratory tract. Methods that involve the upper respiratory tract in collection of specimens entail the hazard of contamination by microbiota resident in the upper respiratory tract. The extrapulmonary approaches of cutting-needle biopsy and needle aspiration of intrathoracic disease have not been impressively productive of etiologic diagnosis of infections. While open-chest surgical biopsy has been a highly effective means to diagnosis, this approach does have special requirements in facilities and technical skills. Percutaneous transtracheal aspiration of tracheo-broncho-pulmonary secretions-exudates has been productive of useful information. Because of inherent simplicity and safety, transtracheal aspiration should precede resort to more demanding, difficult, dangerous procedures.